Bosnian pine (Pinus heldreichii syn. Pinus leucodermis) - Vendramin, Giovanni Giuseppe; Fineschi, S.; Fady, B. (2008)
Technical guidelines are targeted to practical forest managers and provide summarized information on the biology and ecology of tree species, distribution ranges, importance and use, genetic knowledge, threats to genetic diversity and recommendations for long-term genetic conservation. For the full list of Technical guidelines produced, please visit http://www.euforgen.org/publications/technical_guidelines.html